Association of rotating shift work schedules and the use of prescribed sleep medication: A prospective cohort study - Tucker Philip; Härmä Mikko; Ojajärvi Anneli; Kivimäki Mika; Leineweber Constanze; Oksanen Tuula; Salo Paula; Vahtera Jussi (WILEY, 2022)
We examined whether working rotating shifts, with or without night work, is associated with the purchase of prescribed sleep medication, and whether the association is dependent on age. Data were obtained from a longitudinal cohort study of Finnish public sector employees who responded to questions on work schedule and background characteristics in 2000, 2004 and 2008. The data were linked to national register data on redeemed prescriptions of hypnotic and sedative medications, with up to 11 years of follow-up. Age stratified Cox proportional hazard regression models were computed to examine incident use of medication comparing two groups of rotating shift workers (those working shifts that included night shifts and those whose schedules did not include night shifts) with day workers who worked in a similar range of occupations. Shift work with night shifts was associated with increased use of sleep medication in all age groups, after adjustments for sex, occupational status, marital status, alcohol consumption, smoking and physical activity levels (hazard ratio [HR], [95% confidence interval, CI] 1.14 [1.01-1.28] for age group <= 39 years; 1.33 [1.19-1.48] for age group 40-49 years; 1.28 [1.13-1.44] for age group >= 50 years). Shift work without nights was associated with medication use in the two older age groups (HR [95% CI] 1.14 [1.01-1.29] and 1.17 [1.05-1.31] for age groups 40-49 years and >50 years, respectively). These findings suggest that circadian disruption and older age puts rotating shift workers, and especially those who work nights, at increased risk of developing clinically significant levels of sleep problems.